Exploring The Mediating Role Of CSR In The Relationship Between Corporate Governance And Financial Performance - Vuppuluri, Ramakrishna; Pandey, Abhishek (South Eastern European Journal of Public Health, 2025)
This study investigates whether Corporate Social Responsibility (CSR) mediates the relationship between Corporate Governance (CG) and Corporate Financial Performance (CFP). The current literature has extensively examined the individual relationships between CG and CSR as well as between CSR and CFP, while only minimally exploring the interconnections among these variables. The research design employed was quantitative, and data from 55 firms (550 firm-year observations) were analyzed using the PROCESS macro (Model 4) in SPSS. CSR was used as a mediating variable, CG as the independent variable, and CFP as the dependent variable, with company size, debt-equity ratio, firm age, and market capitalization as control factors. This demonstrates that full mediation exists for CSR between CG and CFP as good governance procedures have improved CSR initiatives, resulting in enhanced financial performance outcomes. This study provides governments and corporate leaders with insights into enhancing the sustainability and competitiveness of their CSR outcomes.